Novel Heteroleptic Uranyl(VI) Complexes Incorporating Tetradentate and Bidentate Chelating Ligands: Deviation from the Oyl‐U‐Oyl Linearity. Issue 35 (13th September 2022) - Sethi, Sipun; Panigrahi, Rachita; Mallik, Bhabani S.; Behera, Nabakrushna
Abstract: Two heteroleptic uranyl(VI) complexes [UO2 (L)(phen)] (1 ) and [UO2 (L)(pypzH)] (2 ) [where, H2 L=N2 O2 ‐benzil bis(isonicotinoyl hydrazone) ligand, phen=1, 10‐phenanthroline and pypzH=3‐(2‐pyridylpyrazole)] were synthesized and characterized by elemental analysis, mass spectrometry, UV‐Visible, 1 H NMR, FT‐IR and TGA techniques. The time‐dependent density functional theory (TD‐DFT) calculations of both the complexes were carried out to obtain the insights into the structure and spectral properties. According to results obtained, the title complexes have highly distorted structures deviating from the expected hexagonal bipyramidal structures. The computed results show that the LUMO of the complex is mainly stabilized by uranium. Both the complexes exhibit similar UV‐Visible spectra within the region 325–600 nm with their intense bands at ∼450 nm primarily due to the HOMO→LUMO transitions. A weak absorption band which appears at ∼335 nm for each complex has been attributed to n→π* transition. In contrast to complex 2, the complex 1 exhibits maximum deviation from the Oyl ‐U‐Oyl linearity. Abstract : Heteroleptic uranyl(VI) complexes based on the unique coordination of tetradentate N2 O2 ‐benzil bis(isonicotinoyl hydrazone) and bidentate 1, 10‐phenanthroline/ 3‐(2‐pyridylpyrazole) ligands were synthesized and characterized. Computational calculations of complexes were performed to realize the insights into the structure and spectral properties. Maximum deviation from the Oyl ‐U‐Oyl linearity was observed at the complex that holds phenanthroline entity.